Faculty development on a shoestring : programs to support higher education faculty using little or no resources - Chapman, Diane D.; Bartlett, Michelle E., 1974- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Faculty development is essential for promoting excellence in teaching and research, supporting institutional goals, and creating a culture of continuous learning that benefits both faculty members and students. However, educational institutions do not always allocate adequate resources towards supporting their faculty's professional development, especially from the institutional level. Underfunding this support can lead to the inability to attend conferences to keep up with the latest research and pedagogical practices in their fields, the inability to conduct meaningful research, and lack of access to modern technologies. This in turn can limit faculty growth and harm student learning outcomes. Ultimately, faculty who do not feel supported by their institutions can become disengaged or leave. This book attempts to address the needs of faculty from institutions where there may not be adequate resources to support robust faculty development activities. The chapters are written by faculty development experts in the US and Europe who understand the disparities between institutions and want to share programs that can be implemented for little or no cost. Each chapter provides objective, content, implementation, and evaluation details that can be used to replicate the program at other institutions. The hope is to begin to level the playing field in faculty development through sharing successful low resource programs with proven outcomes"--